DISC Personality and Career Readiness of Gen Z Psychology Students: I/O Psychology in Digital Era - Iranita Hervi Mahardayani; Dhini Rama Dhania (Journal of Educational, Health and Community Psychology, 2025)
The digital era demands career readiness that extends beyond technical competencies, emphasizing adaptive personality traits suited to dynamic organizational contexts. This study aims to map the DISC personality profiles of Generation Z psychology students and analyze their alignment with digital workforce demands in Industrial and Organizational Psychology (I/O Psychology). A descriptive-analytic quantitative design was employed, involving 248 undergraduate students from Universitas Muria Kudus. Data were collected using a validated DISC instrument with acceptable internal consistency (Cronbach’s α = 0.628–0.741), and model fit confirmed by Confirmatory Factor Analysis. Chi-square tests were used to examine associations among DISC categories and demographic variables. Results revealed a dominance of Conscientiousness (C) and Steadiness (S) types across strength, weakness, and total scores, indicating tendencies toward structured thinking, collaboration, and reliability. Significant correlations among DISC dimensions supported personality consistency across contexts, while no significant differences were found by gender, age, or cohort year. These findings underscore the importance of cross-dimensional personality development, particularly Dominance (D) and Influence (I) traits, to enhance adaptability and leadership in digital work environments. The study offers practical implications for integrating personality-based frameworks into I/O Psychology curricula to support holistic career readiness and employability.